AUXETICS AS ENTROPY FILTERS – POSSIBLE APPLICATION - KRZYSZTOF W. WOJCIECHOWSKI (TASK Quarterly, 2016)
In this note a sketch of the idea of applying auxetics to separation of 3He from a mixture of 4He and 3He by using auxetic entropy filters is presented.